Information technologies in geomagnetic investigations of Late Cenozoic Pacific submarine volcanoes - Rashidov V.A.; Romanova I.M.; Bondarenko V.I.; Palueva A.A. (My University, 2010)
The original actual materials collected during the geomagnetic research on the research vessel "Vulkanolog" in 1977-1991 (19 volcanological expeditions) resulted in important contribution into the world data on the structure of Late Cenozoic Pacific submarine volcanoes. The research resulted in a single method analysis of the anomalous magnetic field of submarine volcanoes and volcanic zones within the Kurile, Izu-Bonin, Mariana, Solomon and Kermadec arcs, New Guinean and South China peripheral seas and within the Socorro hot-spot. It is stressed that the Late Cenozoic submarine volcanoes within the arcs show their presence distinctly in the anomalous magnetic field by local anomalies located within the edifices. Their amplitude may reach 3000 nT, and the horizontal gradient of the field may exceed 100 nT/km. The data interpretation of the hydromagnetic survey allowed distinguishing the internal structure of single submarine volcanoes, volcanic massifs and volcanic zones in various Pacific regions. The authors revealed the bodies forming anomalies within the isolated volcanic edifices and submarine volcanic zones. The 2.5D and 3D modeling resulted in the estimation of the body ages and the period of the submarine volcanic activity. Besides the research resulted in estimation of the edifice volumes, scale of submarine volcanic activity and drew the conclusion on the evolution of certain volcanic massifs. In order to classify and visualize the materials on the geomagnetic research we continue to create "Late Cenozoic Pacific submarine volcanoes" information system. Currently the information system includes: The Internet page "Comparative analysis of the materials on geomagnetic research of various manifestation types of the Late Cenozoic submarine volcanism in the Pacific"; "Late Cenozoic Pacific submarine volcanoes" database; GIS "Geomagnetic investigations of various appearance types of Late Cenozoic Pacific submarine volcano activity". The web site http://www.kscnet.ru/ivs/grant/grant_04/index.html contains numerous maps of the anomalous magnetic field, bathymetric and structural maps, fragments of the echo- sounding survey records and continuous acoustic profiling, photos of land volcanoes, references of the Pacific submarine volcanic activity and "Catalogue on the Late Cenozoic Pacific submarine volcanoes" (in Russian). The database on the Late Cenozoic Pacific submarine volcanoes includes location of submarine volcanoes, magnetic behaviors and chemical composition of dredge rocks and volumes of the volcanic edifices. The database is hosted on the IVS FEB RAS server and is available on the following page: http://www.kscnet.ru/ivs/volcanoes/submarine/. The GIS contains maps of the anomalous magnetic field and the volcanic edifices relief. "Late Cenozoic Pacific submarine volcanoes" information system provides researchers with the convenient tools for working with cartographic and attributive data and helps to implement a comprehensive data processing.
Keywords: 20.23.21 Информационно-поисковые системы. Банки данных; 20.23.27 Геоинформационные системы; 38.37.27 Петрография океанических пород и подводный вулканизм; Кальдера Горшкова; Алаид; Пийпа; Среднего о-ва